A3 4 In A Hurry? - Bentley, Bobby; Lebidineuse, Leon; McFahn, Ryan (Physics Special Topics, 2023)
In this paper, we investigated the speed one would have to travel at for a red traffic light to appear green due to the Doppler effect. We determined that if a vehicle was travelling at a speed of 9.7x107 ms-1 (or 30% the speed of light), a red traffic light would appear green due to the Doppler Effect, allowing you to continue on your high-speed journey uninterrupted.